Fibroma of Tendon Sheath Presenting Limited Flexion of the Fingers - Kazuhiro Maeda; Nokitaka Setsu; Yoshiharu Kato; Akira Kawai; Eisuke Kobayashi (Case Reports in Orthopedics)
A 35-year-old Japanese man presented with a 1-month history of limited flexion and radiating pain in the left middle and ring fingers. A physical examination revealed a hard nodular mass in his left palm. Magnetic resonance imaging showed a 2 × 1.5 × 1 cm mass of low intensity on T1-weighted images and high intensity on T2-weighted images and gadolinium enhancement. The tumor was marginally resected, adhering to the flexor digitorum profundus of both the third and fourth fingers. The histological diagnosis was fibroma of tendon sheath. After the surgery, the range of motion and hand function were improved. No recurrence has been observed. Fibroma of tendon sheath usually arises on the fingers and hands with strong attachment to the tendon or tendon sheath. The tumor in the present case probably limited the range of flexion of the fingers by obstruction of the transverse carpal ligament.